Tempestatis obsequium in principem : pouvoir cosmocratique et vertus de l’empereur dans les Panegyrici Latini (IIIe-IVe siècles) - Zugravu, Nelu (Classica - Revista Brasileira de Estudos Clássicos, 2021)
Among the sources that reflect the transformations occurred in the imperial ideology during the 3rd-4th centuries, we find the speeches uttered between 289 and 389 in official and solemn circumstances by orators from Gallia (some of them anonymous), reunited since the Antiquity in the corpus entitled Panegyrici Latini. A special place in this respect is occupied by the divine nature of the emperor. The biography on the matter is rather consistent, but we may still add to the discussion an aspect that has not been approached thus far, and that I will approach in this paper, namely the relation between the princeps and the elements of nature. The analysis of the paragraphs concerning the control over the physical universe by the sovereigns allows the emphasis on aesthetical formulas through which the orators have accentuated certain defining elements of the ideology conveyed using their discourses – the cosmocratic rulership, exceptional civilian and military powers, legitimate election, the consensus between the Court and the provincial political circles. The sections of the paper are based on these aspects: 1. Maximianus – fortitudo; fortuna; felicitas; 2. Constantius and the providentia; 3. Constantine – utilitas publica; virtus; princeps salutaris; 4. Theodosius and the meritocratic principality.